Analisis Kritis Opini Syariah Terhadap Aset Kripto Dalam Perspektif Ekonomi Syariah - Putri, Berliana; Amelia, Nur; Iskandar, Iskandar; Amalia, Nala; Lismawati, Lismawati (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study aims to critically analyze sharia opinion on crypto assets from a sharia economic perspective, specifically in assessing the legality of their use based on the principles of Islamic jurisprudence (fiqh) in muamalah (Islamic transactions). The method used is a literature study with a qualitative-descriptive approach, examining various secondary sources such as fatwas from the Indonesian Ulema Council (MUI), the results of the Bahtsul Masail forum, scientific journals, and the opinions of contemporary scholars. The results show that there are differences of opinion among scholars. Some scholars prohibit the use of crypto assets because they are considered to contain elements of gharar (uncertainty), maysir (speculation or gambling), and lack a clear underlying asset. However, others permit crypto assets as long as they are used as commodities (sil'ah), not as a means of payment, and do not involve elements of fraud or deception. Therefore, from a sharia economic perspective, crypto assets can be considered halal if they meet the criteria of benefit, clear ownership, and are subject to strict regulations to prevent practices that conflict with sharia principles